Study of biochemical markers in iron deficiency anemia - Deokar, Smita A.; Rai, Pooja S. K.; Bakshi, Amruta A.; Rai, Anita B. (International Journal of Research in Medical Sciences, 2017)
Background: The present study was aimed to study alterations in levels of oxidants and antioxidants in iron deficiency anemia (IDA). Methods: 30 patients of IDA in age group of 20-50 and 30 healthy subjects were included for study. Serum Iron, TIBC & Hb% were estimated to diagnose IDA. Serum Malondialdehyde (MDA), Nitric oxide (NO) as an oxidants & Superoxide dismutase (SOD), vitamin E, vitamin C, Zinc (Zn) levels as antioxidants were estimated. Results: Significant decreased levels of Hb%, serum iron, SOD, Vitamin C, vitamin E, Zn were found. TIBC, MDA, NO were significantly increased as compared to controls. Conclusion: The normal adult erythrocytes can resist oxidative stress by several antioxidant defense systems. In IDA, oxidative stress causes lipid peroxidation and membrane damage. So antioxidants can be used as a marker for prevention of membrane damage due to oxidative stress.